Does Disease-Irrelevant Intrathecal Synthesis in Multiple Sclerosis Make Sense in the Light of Tertiary Lymphoid Organs? - Bonnan, Mickael (Frontiers in Neurology, 2014)
Although partly disease-irrelevant, intrathecal Ig synthesis is a typical feature of multiple sclerosis (MS) and is driven by the tertiary lymphoid organs (TLO). A long-known hallmark of this non-specific intrathecal synthesis is the MRZ pattern, an intrathecal synthesis of Ig against measles, rubella and zoster viruses, which could also be involved in a wide range of pathogens. However, this non-specific synthesis is highly problematic since brain TLO should not be able to drive the clonal expansion of lymphocytes against alien antigens that are thought to be absent in MS brain. We propose to explain the paradox of non-specific intrathecal synthesis by discussing the natural properties of TLO. In fact, besides local antigen-driven clonal expansion, circulating plasmablasts and plasma cells (PC) are non-specifically recruited from blood and gain access to survival niches in the inflammatory CNS. This mechanism, which has been described in other inflammatory disorders, takes place in the TLO. As a consequence, PCs recruited in brain mirror the individual’s history of immunization and intrathecal synthesis of IgG in MS may target a broad range of common infectious agents, a hypothesis in line with epidemiological data. Moreover, the immunization schedule and its timing may interfere with PC recruitment. If this hypothesis is correct, the reaction against EBV appears paradoxical: although early infection of MS patients is systematic, intrathecal synthesis is far lower than expected, suggesting a crucial interaction between MS onset and timing of EBV infection. A growing body of evidence suggests that the non-specific intrathecal synthesis observed in MS is also common in many chronic CNS inflammatory disorders. Assuming that cortical TLO in MS are associated with typical sub-pial lesions, we have coined the concept of ‘TLO-pathy’ to describe these lesions and take examples of them from non-MS disorders.